”Hvor viljen er lov og fornuften i eksil”: Fællesskabets grænse i sørejsens fortælling, ca. 1600 - Heinsen, Johan (Academic Quarter | Akademisk kvarter, 2011)
Another historical transgression of a quite different kind is found in Johan Heinsen's article Hvor viljen er lov og fornuften i eksil, where we see how the retelling of a historical incident – Sir Francis Drake executing Thomas Doughty in 1578 – engages in establishing the boundaries of community and the limits of historiography in connection with the seafaring communities. The marginalized outsider, in this case John Cooke, becomes the means to both challenge and establish these boundaries.